Baycare Health System's Approach to Implement an Evidence‐Based Sepsis Mortality Reduction Program. Issue 8 (14th September 2018) - Gupta, Chhavi; Held, Jeffrey; Munro, Jacqueline C.; Hager, Alison; Lapham, Robin K.; Powers, Michelle; Lynn, Nancy; Gupta, Kul; Bean, Jo L.; Vaaler, Mark D.
Abstract: Sepsis is the 10th leading cause of death in the United States. A 14‐hospital health system formed a multidisciplinary team to build an evidence‐based sepsis‐mortality reduction program (SMRP). SMRP leads to a statistically significant decrease in sepsis mortality, significant improvement in compliance with SEP‐1 (core measure), and statistically significant negative correlation between SEP‐1 bundle compliance rates and the sepsis‐mortality rates. Patients who received the SEP‐1 bundle were 51% more likely to survive.